DAILY BLOOD PRESSURE PARAMETERS AND STRUCTURAL AND FUNCTIONAL CHANGES IN THE MYOCARDIUM OF PATIENTS WITH HYPERTENSION AND FREQUENT VENTRICULAR EXTRASYSTOLE - Ivankova, A.V.; Kuzminova, N.V.; Lozinsky, S.E.; Kniazkova, I.I.; Ivanova, E.I.; Shkarivsky, Yu.L.; Romanova, V.O. (World of Medicine and Biology, 2024)
We examined 50 patients with stage II hypertension and frequent symptomatic ventricular extrasystoles and 32 patients with stage II hypertension without any cardiac arrhythmias. All patients underwent a comprehensive clinical and instrumental examination, daily blood pressure monitoring, and echocardiographic examination. It was determined that patients with ventricular extrasystoles had significantly (p